Public Participation Based Learning Approach on Science and Technology to Solve Water Supply Problems in Sadiang Community, Phetchabun Province - Baowthongkum, Namfon; Patummas, Damruswit (Area Based Development Research Journal, 2019)
This research integrates the public participation approach with teaching and learning in Basic Chemistry course of the science and technology content area. The 30 samples of the third-year general science students in Faculty of Education, Phetchabun Rajabhat University apply knowledge to community in Sadiang sub-district, Muang district, Phetchabun province. The aims are to develop learning and innovation skills, Information skills, life skills and career skills by using participation action research. The learning process has 6 steps: 1) community information 2) self-learning 3) self-reliance 4) knowledge sustainability 5) knowledge transfer and 6) learning outside the community. The research results indicate that students and community collaborate to create water filters from natural materials, namely rocks, gravel, sand and charcoal. Evaluation of 21st century skills of students is conducted by authentic assessment, which includes evaluation of innovation efficiency, satisfaction of community, and reflection activity of students and community. The findings show a high level of community’s satisfaction with the efficiency of the water filter as well as the students’ performance. Students reflect their self-confidence and self-esteem. They are able to apply scientific knowledge to daily life while working in team to solve problems. This illustrates that the students have developed the 21st century skills through the public participation based approach integrated to the course.